TOURISM AND SUSTAINABILITY AT THE CROSSROADS: GLOBAL–LOCAL INTERACTIONS IN BIRA, BULUKUMBA - Hasrul Hasrul; Amirullah Amirullah; Nurmila Nurmila (Politeknik Pariwisata Makassar, 2025)
Tourism in coastal destinations often embodies the tension between global influences and local realities. This paper explores the sustainable transformation of marine tourism in Bira, Bulukumba, one of Indonesia’s prominent coastal resorts. The study investigates how global sustainability frameworks intersect with local community practices and how these dynamics shape the pathways toward responsible tourism development. Using a qualitative case study approach, the research employs in-depth interviews with stakeholders, field observations, and secondary data analysis. Findings reveal that global sustainability discourses—such as regenerative tourism, eco-certifications, and international market demands—have gradually influenced the operational models of Bira’s resorts. At the same time, local communities emphasize cultural preservation, livelihoods, and traditional marine practices. The intersection of these perspectives has generated both opportunities and challenges: while eco-friendly initiatives and community-based tourism programs have emerged, issues of waste management, resource conflicts, and cultural commodification remain significant obstacles. The study concludes that Bira stands at a critical crossroads where global sustainability goals and local identity must be harmonized. The paper recommends collaborative governance, capacity building for local stakeholders, and integrated coastal management to ensure tourism contributes positively to ecological resilience and community well-being.